Mishnah's theology of tithing : a study of tractate Maaserot - Jaffee, Martin S. (Brown Judaic studies ;, 2020)
"This study is a translation and exegesis of Mishnah ' s Tractate Maaserot (Tithes) and its corresponding tractate of Tosefta . The goal of the volume is to understand the laws of Maaserot as the tractate 's creator(s) intended them to be understood."--Provided by publisher